Eksplorasi Faktor yang Mempengaruhi Loyalitas Konsumen Ojek Online - Mohammad Rizal Gaffar; Mamun Sutisna (Akademi Sekretari Manajemen Taruna Bakti, 2020)
Ojek Online is a motorbike based public transportation application. Gojek and Grab is the top ojek online in Indonesia. There are still many local startups in the ojek online business such as Ladyjek, Blu-jek, and Motorcycle taxi. They are unable to compete because their rates are less competitive. This is because the capital owned is not too big to do the